PARÂMETROS METABÓLICOS, PERIODONTAIS E NÍVEIS DE CITOCINAS EM FLUIDO CREVICULAR GENGIVAL DE INDIVÍDUOS COM SÍNDROME DE DOWN. - MOUCHREK, Monique Maria Melo (2020)
Periodontal disease (PD) is a chronic inflammatory and infectious alteration of the gums and supporting tissues of the teeth. The persistence of microbial biofilm in close proximity to periodontal tissues induces an antigenic stimulus that activates the host's inflammatory mediators, which, like cytokines, have been associated with tissue destruction and bone resorption. The progression of PD is not only induced by these microbial agents, it is also dependent on the host's response and some individuals may have an altered immune response, such as individuals with Down Syndrome (DS), who have a high prevalence of PD. In this context, individuals with DS, due to comorbidities resulting from the syndrome, which became more frequent with the increase in life expectancy of this population, may present a metabolic condition and compromised immune-inflammatory response contributing to the onset of oral diseases, involving periodontal disease and tooth loss. Thus, Chapter I of this thesis, Relationship between metabolic and periodontal parameters in individuals with Down Syndrome, investigated the relationship between metabolic condition indicators (anthropometric measurements, blood pressure and serum markers) and periodontal parameters in individuals with Down Syndrome (DS). The cross-sectional study, carried out with 49 individuals with DS. The volunteers underwent periodontal examination to measure the probing depth (PS), the clinical attachment level (CAL), the gingival bleeding index (GBI) and the visible plaque index (VPI). Periodontitis was classified as mild, moderate or severe. The participants' metabolic condition was determined through the analysis of anthropometric parameters: body mass index, waist circumference, arm and arm muscle, tricipital skin fold, hip and waist circumference, blood pressure measurement and blood collection for dosage of serum markers. The data were analyzed using the Mann-Whitney test and Spearman's correlation coefficient. Moderate or severe periodontitis was detected in 63.3% of the sample, with high VPI (54.6 ± 35.8) and GBI (42.4 ± 33.3) values. Higher mean corpuscular hemoglobin (MCH) and lower mean corpuscular volume (MCV) levels were detected in individuals with moderate or severe periodontitis (P < 0.001). Arm circumference measurements and HDL cholesterol levels were inversely correlated with some periodontal variables. Moreover, hemoglobin levels were directly correlated with the percentage of sites with CAL ≥ 4 mm. Our findings suggest that periodontal parameters may be related to markers of metabolic condition in individuals with DS. And Chapter II, Levels of cytokines in the gingival crevicular fluid and its association with periodontal parameters in individuals with Down syndrome. Case-control study, evaluated the levels of cytokines IL-1β, IL-4, IL-6, IL-17a, TNF-α and IFN-γ in gingival crevicular fluid (GCF) of people with Down Syndrome (DS), in periodontal sites and analyzed its relationship with periodontal clinical parameters. A case-control study, carried out at the Federal University of Maranhão, with 48 individuals with DS and 32 individuals without syndrome. Participants underwent periodontal examination with measurement of probing depth (PD), clinical attachment level (CAL), gingival bleeding index (GBI) and visible plaque index (VPI). The sites were classified as mild, moderate and severe. The collection of GCF was performed in all light sites and, when present, in moderate and severe sites, for analysis of the level of cytokines. The cytokines IL-1β, IL-4, IL-6, IL-17a, TNF-α and IFN-γ were quantified using the automated Luminex® analyzer system. Data were analyzed using the Shapiro-Wilk test for normal distribution of continuous variables, the Chi-square test or Fisher's exact test for comparative analysis of categorical variables and Mann-Whitney for comparative analysis of continuous variables between study groups. The group with DS presented greater severity of periodontal disease, with moderate and severe periodontitis, respectively in 38.8% and 24.5% of the individuals, while the controls represented 28.1% and 12.5% in the same categories of the group. In addition, it showed statistically higher concentrations of IFN-γ, IL-17a, IL-1β, IL-4, IL-6 in the GCF when compared to the control group. When evaluated separately according to PD, we observed a higher concentration of IFN-γ, IL-17a, IL-1β and IL-6 in shallow pockets and of IL-17a, IL-1β and IL-6 in deep pockets in the syndromic individuals. The DS group showed a significant direct correlation between IL-1β and an inverse correlation between IFN- γ and IL-14 with all periodontal parameters. We were able to observe that individuals with DS have higher periodontal involvement, which can be partly explained by higher levels of cytokines in the GCF, even in sites with periodontal clinical parameters similar to nonsyndromic individuals. These data reinforce the concept of an altered and less effective immune response in this population in the face of the periodontal microbial challenge.